Bermain Game Online berhubungan dengan Perilaku Caring pada Mahasiswa Keperawatan UNSOED - Ratna Sari; Eva Rahayu; Akhyarul Anam (Journal of Bionursing, 2022)
Introduction: Online games attract a lot of public attention, one of which is from the students. Playing online games is possible to influence the caring behavior of nursing students.The purpose of this study was to determine the relationship between playing online games with caring behavior in Nursing Department students at Jenderal Sudirman University (UNSOED).Methods: The method used in this research is quantitative with a correlational design using a cross sectional approach. Respondents involved in this study were 46 students of the Department of Nursing at Jenderal Soedirman University who were selected by total sampling technique. Analysis of the data used is the Somers'd test.Results: The majority of Nursing Department students play online games at a moderate level, which is 60.9% and the caring behavior of students is mostly in the caring category as much as 71.7%. Somers'd non-parametric statistical test results show that the p-value is 0.228 (p> 0.05), which means that playing online games is not related to caring behavior in UNSOED Nursing students.Discussion: Playing online games can be influenced by several factors such as individual factors, psychological factors, and group factors. High humanistic and altruistic attitudes (91.5%) are able to control one's attitude to be more controlled, so that caring behavior is not affected by online gamesConclusion: Playing online games is not related to caring behavior of UNSOED Nursing students.